A balancing act between economic growth and sustainable development: Historical trajectory through the lens of development indicators. (23rd June 2022) - Hirai, Tadashi
Abstract: The evolution of the development discourse is profoundly political. Despite a range of innovations the situation remains much the same, and has led over time to the dominance of the economic growth model. Whilst academic/ideological vigour, policy relevance and institutional support, together with intellectual independence, are essential; too radical an alternative approach would be dismissed by mainstream opinion, either by design or neglect. To survive and to remain influential, any alternative requires the mainstream to engage with it for political feasibility. The development discourse has thus evolved through a delicate balancing act, acknowledging a need for a cautiously optimistic outlook. By tracing changes in two approaches to development (basic needs and human development) and in two global development goals (millennium development goals and sustainable development goals) through their selection and use of indicators, this article explores both the explicit and the implicit power of the mainstream in the past and present alternatives.